The complete chloroplast genome of Malva cathayensis M.G.Gilbert, Y.Tang & Dorr 2007 and its phylogenetic analysis - Shuming Zhang; Kaihua Zhang; Yuting Jiao; Junfei Liu; Weihan Yuan; Liqiang Wang (Mitochondrial DNA. Part B. Resources)
Malva cathayensis, a wild medicinal and edible Malvaceae species, lacked genomic data until now. In this study, we presented its first complete chloroplast genome (158,793 bp), featuring a quadripartite structure: 87,215 bp LSC, 20,766 bp SSC, and two 25,406 bp IRs. The genome contains 129 genes (85 protein-coding, 36 tRNA, 8 rRNA) with 37.1% GC content. Phylogenetic analysis revealed two Malva clades, with M. cathayensis grouping alongside M. crispa, M. verticillata, and M. parviflora. This study provides essential molecular data for Malva's evolutionary relationships and diversification, enabling future comparative genomic research in this genus.